Adjust genetic algorithm parameter by fuzzy system - Noshadi, Tayebe; Dadvar, Marzieh; Mirza, Nastaran; Shamseddini, Shima (Ciência e Natura, 2015)
Genetic algorithm is one of the random searches algorithm. Genetic algorithm is a method that uses genetic evolution as a model of problem solving. Genetic algorithm for selecting the best population, but the choices are not as heuristic information to be used in specific issues. In order to obtain optimal solutions and efficient use of fuzzy systems with heuristic rules that we would aim to increase the efficiency of parallel genetic algorithms using fuzzy logic immigration, which in fact do this by optimizing the parameters compared with the use of fuzzy system is done.